Modelling Exciting Writing A guide for primary teaching - Bushnell, Adam; Bushnell, Adam; Smith, Rob; Waugh, David (SAGE Publications, 2018)
In order to teach writing effectively, teachers must be able to model writing effectively to children. The Primary National Curriculum sets challenging expectations for the teaching of writing. Children must master the process of composition, redrafting, editing and writing final pieces. Increased emphasis on spelling, punctuation and grammar may leave some teachers and trainee teachers lacking ideas for developing children's writing beyond transcription and into composition. It is important that they are able to demonstrate their knowledge and understanding, as well as the practical applications of both transcriptional and compositional aspects of writing.